Da crise normal ao risco: produções da adolescência nos cenários da saúde mental no Brasil - Magalhães, Ana Clara [UNESP] (2014)
The aim of this dissertation was to problematize the adolescence's production as and an object of scientific investigation and social intervention at the field of mental health's in Brazil. With this we seek to seize the lines of force which compose the historical process of construction of the adolescence and of the current scenario of the pathologization and psychiatrization of adolescent's behavior. For this, we (re)construct two major scenarios of Brazilian mental health's history: from 19th century to the finals of 20th century, and from the finals of 20th century to the current century (21st). The execution of this proposal was supported in a documentation corpus referring to the current proposals of mental health care in Brazil, namely: Development Psychiatry and Psychosocial Attention; this documentation involves laws, ordinances, decrees, manuals, booklets, reports and divulges materials. As an theoretical-methodological reference our inspiration was the archeo-genealogy perspective of Michel Foucault, since license us to do a critical problematization of the present and the history from an analysis which, without pretensions of affirm essences and universalities, focuses on the historical, political and socials engendered involved in the productions and practices of medicine, psychology, psychiatry and justice about the adolescence. In that way, this dissertation aimed less to presents answer than fortify the questions about the hegemony practices on mental health care in Brazil, and also charges resistance's strategies to the affirmation practices of care and attention to adolescence which consider mental health as a complex social process